2011
DOI: 10.4084/mjhid.2011.024
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Disease and Venous Thromboembolism

Abstract: Hemoglobin S in homozygous state or in combination with one of the structural variants of Hb D-Punjab, Hb O-Arab, Hb C or β-thalassemia mutation results in sickle cell disease (SCD) that is characterized by chronic hemolytic anemia and tissue injury secondary to vasooclusion. A chronic hypercoagulable state in SCD has been established with the increased risk of thromboembolic complications in these patients. The goal of present review is to survey of the literature related to thromboembolic events and genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 78 publications
(84 reference statements)
0
22
0
Order By: Relevance
“…This coagulation is brought about by activated protein C resistance, 90–95% cases of which are accounted by heterozygosity for factor V Leiden mutation. Both these events may lead to thrombo‐occlusive complications among patients with SCD . As thrombosis plays significant role in pathophysiology of SCD clinical manifestations, patients with SCD in the present study having mutant variants of FVL and MTHFR genes have shown significant prevalence of fatigue, fever, pain in chest, abdomen, bone joints along with early onset of clinical manifestations making these patients frequent dependent on blood transfusion to relieve painful crises.…”
Section: Discussionmentioning
confidence: 69%
“…This coagulation is brought about by activated protein C resistance, 90–95% cases of which are accounted by heterozygosity for factor V Leiden mutation. Both these events may lead to thrombo‐occlusive complications among patients with SCD . As thrombosis plays significant role in pathophysiology of SCD clinical manifestations, patients with SCD in the present study having mutant variants of FVL and MTHFR genes have shown significant prevalence of fatigue, fever, pain in chest, abdomen, bone joints along with early onset of clinical manifestations making these patients frequent dependent on blood transfusion to relieve painful crises.…”
Section: Discussionmentioning
confidence: 69%
“…Sickle cell disease (SCD) results from the homozygous state of the mutation, or a compound heterozygous state with one of structural variants of Hb D-Punjab, Hb O-Arab, Hb C, or β -thalassemia mutation in the other β -genes [16, 17]. …”
Section: Structural Variantsmentioning
confidence: 99%
“…[2] Many another factors also have been reported to contribute to the hypercoagulable state of patients with SCA such as hyperfibrinogenemia, increased concentration of von Will brand factor and decreased plasma levels of protein C, protein S, and antithrombin III, increased prothrombin fragment, thrombin-antithrombin complexes, plasma fibrinogen products, D-dimer, and decreased coagulation factor V.[16]…”
Section: Discussionmentioning
confidence: 99%